Deteksi Dini Faktor Risiko Penyakit Jantung dan Pembuluh Darah, Hubungan Antara Obesitas, Aktivitas Fisik dan Kolesterol Total di Kecamatan Kertapati, Kota Palembang - Achmad Ridwanmo; Mariatul Fadillah; Tri Hari Irfani (Jurnal Epidemiologi Kesehatan Komunitas, 2020)
Background: Cardiovascular disease is the first cause of death in Indonesia. The prevalence of stroke based on diagnosis rose from 7 (2013) to 10.9 per mil (2018), The prevalence of cardiovascular disease is 1.5 per mil. Research on the detection of risk factors for cardiovascular disease using a cardiovascular risk score according to WHO and the Jakarta Score has never been conducted in Palembang. The purpose of this study is to conduct early detection of risk factors to predict cardiovascular disease in the next 10 years, and find out the relationship between obesity, physical activity to reduce cholesterol.Methods: This research was conducted using an observational analytic study with cross sectional design and multistage sampling method. Samples in this study were 126 people from 3 village in Kertapati district in Palembang City.Result: The research showed that high level risk to cardiovascular disease in 10 years by using WHO non laboratory, laboratory and Jakarta Score was 4,8%, 6,7%, 61,9% respectively. Whereas, the moderate risk was 20%, 26,2% and 25,4%. There was no association between obesity and total cholesterol (p=0.682), but there was an association between physical activity and total cholesterol (p=0.030, OR 3,1). Moreover, there was a total cholesterol’s mean difference between none/mild, moderate, and severe physical activity that is 36,6 mg/dl (t test, p-value: 0,005).Conclusion: Lack of physical activity could be the one of cholesterol risk factor. Therefore, doing the physical activity could prevent the cardiovascular disease.